﻿A new species of feather-tailed leaf-toed gecko, Kolekanos Heinicke, Daza, Greenbaum, Jackman, Bauer, 2014 (Squamata, Gekkonidae) from the poorly explored savannah of western Angola - Javier Lobón-Rovira; Werner Conradie; Ninda L. Baptista; Pedro Vaz Pinto (ZooKeys, 2022)
We here describe a new species of feather-tailed leaf-toed gecko, Kolekanos, from southern Benguela Province, Angola, based on morphological and osteological evidence, supported by phylogenetic analysis of mitochondrial data. The new species adds to the rapidly growing and newly-recognised endemic biodiversity of Angola, doubling the number of Kolekanos species, breaking the pattern observed within other closely-related African members of a clade of circum-Indian Ocean leaf-toed geckos – Ramigekko, Cryptactites and Afrogecko – all of which are presently monotypic. The new species is easily distinguished from K. plumicaudus, based on spine-like (as opposed to feather-like) scales on the margins of the original tail. Phylogenetic analyses also recovered the new taxon as monophyletic, with a well-supported sister relationship to K. plumicaudus, from which it differs by a substantial 24.1% NADH-dehydrogenase subunit 2 mitochondrial gene uncorrected p-distance.